Infrared micro-spectroscopy for cyto-pathological classification of esophageal cells. Issue 7 (16th January 2015) - Townsend, Douglas; Miljković, Miloš; Bird, Benjamin; Lenau, Kathleen; Old, Oliver; Almond, Max; Kendall, Catherine; Lloyd, Gavin; Shepherd, Neil; Barr, Hugh; Stone, Nick; Diem, Max
Abstract : We report results from a study utilizing infrared spectral cytopathology (SCP) to detect abnormalities in exfoliated esophageal cells. Abstract : We report results from a study utilizing infrared spectral cytopathology (SCP) to detect abnormalities in exfoliated esophageal cells. SCP has been developed over the past decade as an ancillary tool to classical cytopathology. In SCP, the biochemical composition of individual cells is probed by collecting infrared absorption spectra from each individual, unstained cell, and correlating the observed spectral patterns, and the variations therein, against classical diagnostic methods to obtain an objective, machine-based classification of cells. In the past, SCP has been applied to the analysis and classification of cells exfoliated from the cervix and the oral cavity. In these studies, it was established that SCP can distinguish normal and abnormal cell types. Furthermore, SCP can differentiate between truly normal cells, and cells with normal morphology from the vicinity of abnormalities. Thus, SCP may be a valuable tool for the screening of early stages of dysplasia and pre-cancer.